Working with global english: the experience of english language teachers in a University Language College - Peter Kell,; Gillian Vogl, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Through in-depth interviews and focus groups with English Language teachers employed at a university bridging college, this paper explores the challenges that teachers face in preparing international students for university life in Australia. Findings from this research suggest that the narrow business focused objectives of the English Language market undermine more holistic approaches to teaching English. A more holistic approach is required to respond to the social and cultural needs of students while they are studying in Australia. Nevertheless, this research suggests that regardless of the instrumental and reductionist neo liberal philosophy which informs these programs, meaningful intercultural dialogue, critical thinking and some holistic learning does take place.